Surgical Decision Making Beyond the Evidence Based Surgery - Latifi, Rifat (Springer International Publishing : Imprint: Springer, 2016)
This text provides a comprehensive and state-of-the-art overview of the major issues specific to the surgical decision-making process. These include patient's anatomy and pathophysiology as well as the magnitude of the injury at hand, the surgeon's own physiologic and mental status, training and experience, and many other factors such as creativity, leadership skills, and overall "biochemistry" of the environment. The text reviews theoretical as well as objective information that surgeons use to make intraoperative decisions in situations, often with very limited data; decisions that will decide between a patient's living or dying, such as in trauma surgery and other complex surgeries. How surgeons choose one technical approach over another in these situations is covered. This book fills a critical need for resource materials on these topics and includes both theoretical as well as practical presentations of many typical patients seen in operating rooms around the world. Surgical Decision Making: Beyond the Evidence Based Surgery is written by academic and clinical practicing surgeons that face intraoperative decision situations on a daily basis and therefore provides a unique and valuable resource in the field for surgeons currently in training and for those already in clinical or research practice. .